PENGUATAN LITERASI DIGITAL DALAM PENDIDIKAN AGAMA ISLAM SEBAGAI RESPON TERGADAP DISINFORMASI KEAGAMAAN DI ERA SOCIETY 5.0 - Silpa; Sugesti, Vina Nanda; Sunariyah; A. Gani; Kesuma, Guntur Cahaya; Amirudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Literacy is a fundamental foundation for intellectual development and civilization building. In Islamic perspective, literacy is not merely defined as the ability to read and write, but also as a transformative process in the pursuit of knowledge. This article aims to analyze the urgency of literacy in prophetic educational traditions (hadith tarbawi), focusing on reading, writing, and the pursuit of knowledge. This study employs a qualitative approach using library research. Primary data were derived from major hadith collections such as Shahih al-Bukhari and Shahih Muslim, while secondary sources include accredited journals and recent Islamic education books. Data were analyzed using descriptive-analytical and thematic approaches. The findings reveal that hadith tarbawi positions literacy as both a spiritual and social obligation that contributes to character formation and civilizational advancement. Reading and writing traditions function as instruments for knowledge transmission, while the pursuit of knowledge is considered a path toward worldly and eternal success. The concept of literacy in hadith tarbawi remains highly relevant in addressing contemporary digital-era literacy challenges. Keywords: Literacy, Hadith Tarbawi, Islamic Education, Knowledge Tradition